Effects of aligned magneticfield and radiation on the flow of ferrofluids over a flat plate with non-uniform heat source/sink - Sandeep N; Raju CSK; Sulochana C; Sugunamma V (Chemical Engineering Diponegoro University, 2015)
In this study we analyzed the influence of radiation and aligned magneticfield on the flow of ferrofluids over a flat plate in presence of non-uniform heat source/sink and slip velocity. We considered Fe3O4 magnetic nano particles embedded within the two types of base fluids namely water and kerosene. The governing partial differential equations are transformed into nonlinear ordinary differential equations by using similarity transformation and solved numerically using bvp5c Matlab package. The effects of dimensionless quantities on the flow and temperature profiles along with the friction factor and Nusselt number is discussed and presented through graphs and tables. It is found that present results have an excellent agreement with the existed studies under some special assumptions. Results indicate that a raise in the aligned angle enhances the skin friction coefficient and heat transfer rate.